The steady-state impedance operator of a linear periodically time-varying one-port network and its determination - Kłosiński, Radosław (Zielona Góra: Uniwersytet Zielonogórski)
The main subject of the paper is the description and determination of the impedance operator of a linear periodically time-varying (LPTV) one-port network in the steady-state. If the one-port network parameters and the supply vary periodically with the same period, the network reaches a periodic steady state. However, the sinusoidal supply may induce a nonsinusoidal voltage or current.
Keywords: periodically time-varying impedance; periodic steady state; linear periodically time-varying system; circular parametric operator; harmonics aliasing; identification